2015
DOI: 10.1371/journal.pone.0131632
|View full text |Cite
|
Sign up to set email alerts
|

Do Bells Affect Behaviour and Heart Rate Variability in Grazing Dairy Cows?

Abstract: In alpine regions cows are often equipped with bells. The present study investigated the impact of wearing a bell on behaviour and heart rate variability in dairy cows. Nineteen non-lactating Brown-Swiss cows with bell experience were assigned to three different treatments. For 3 days each, cows were equipped with no bell (control), with a bell with inactivated clapper (silent bell) or with a functional bell (functional bell). The bells weighed 5.5 kg and had frequencies between 532 Hz and 2.8 kHz and amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…Nevertheless, as soon as they were familiar with the new condition they were submitted to, they were able to execute their basic activities normally. Contrary to the effect presented here and with the results of Enriquez-Hidalgo et al ( 26), Johns et al (30) reported that cows did not habituate to the use of bells, even though they had previous experience to bells, since lying time and lying bout duration were decreasing even more after some days. These contrary results highlight the fact that cows are able to adapt to something unknown as long as it is not stressful to them.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, as soon as they were familiar with the new condition they were submitted to, they were able to execute their basic activities normally. Contrary to the effect presented here and with the results of Enriquez-Hidalgo et al ( 26), Johns et al (30) reported that cows did not habituate to the use of bells, even though they had previous experience to bells, since lying time and lying bout duration were decreasing even more after some days. These contrary results highlight the fact that cows are able to adapt to something unknown as long as it is not stressful to them.…”
Section: Discussioncontrasting
confidence: 99%
“…By contrast, standing and locomotion result in varying acceleration values ( 45 ). The accelerometer has previously been used to record lying behavior in cows ( 46 48 ) and goats ( 49 ). Additionally, the reliability of our data was validated by comparing the indicated lying bouts of three randomly chosen horses during the first 24 h of data collection with continuously recorded video footage.…”
Section: Methodsmentioning
confidence: 99%
“…The amplitudes of cowbells that are traditionally used on Alpine pastures vary between 90 and 113 dB ( 1 ). However, we did not measure the amplitudes of the bells that the experienced cows were wearing during pasture season.…”
Section: Discussionmentioning
confidence: 99%
“…In alpine regions, cows are often equipped with a bell throughout the summer season to ensure that farmers can locate their animals on the wide alpine pastures, many areas that are obstructed from view. The chime of these cowbells is characterized by high and varying amplitudes from 90 to 113 dB at a distance of 20 cm, the approximated distance between the bell and the cows’ ears ( 1 ). Goats have been found to show higher behavioral arousal when being exposed to the playback of a bell compared to the playback of a uniform sinusoidal sound, indicating that the bell sound might be more aversive to goats than the uniform sound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation